Pengaruh Manajemen terhadap Peningkatan Kualitas Tahfidz Al-Quran di Sekolah Alam Tahfidz Qur’an Majalengka - Nisa, Sofiyatun; Aziz, Ali (Tadbir: Jurnal Manajemen Dakwah, 2023)
The purpose of this study is determine how much influence planning, organizing, implementing and monitoring the quality of tahfidz Al-Qur’an. The method used in this study is a survey method with a quantitative approach, using da’wah management theory. Based on the joint test, it can be stated that the significance value in the F test is 0.000 < 0.05, then the value of fcount > ftable is 84,887 > 2.53 which is obtained for the variables X1, and X2, X3, and X4. This shows that there is a significant effect of the independent variable simultaneously on the dependent variable. the magnitude of the influence given by the management on the quality of tahfidz Al-Qur’an is 93.1%.